An Invariant Form of the Euler-Lagrange Operator - Milewski, Jan (Журнал математичної фізики, аналізу, геометрії, 2008)
We define a class of almost S(M)-multilinear maps. The Euler-Lagrange operator is given by means of the trace of an almost S(M)-bilinear map.Mathematics Subject Classification: 49Q99, 58A20, 58C35.